Aspectos formativos do pedagogo bilíngue na educação de surdos - Zancul, Beatriz Gili (Universidade Federal de São Carlos, 2025)
The education of deaf individuals in Brazil is supported by Law N°. 10.436/2002, which recognized Brazilian Sign Language (Libras) as a means of communication and expression for the deaf community, and Decree 5.626/2005, which defined and defended bilingual education, ensuring the right of deaf students to education and accessible teaching. Thus, Libras is the primary method of communication and expression for deaf people in Brazil, making the training of qualified teachers for this area crucial, as they must know and use the language. Teachers need to be capable of teaching, feeling confident in their command of sign language as a means of communication with their deaf students. Therefore, this thesis aims to investigate the formative aspects of educators who work in deaf education. The work adopts a socio-anthropological perspective on deafness, understanding it as a linguistic and cultural difference, using the term "Deaf" to refer to individuals with hearing loss who adopt Sign Language as their first language. The methodology used was a literature review based on various works addressing bilingual education for the deaf and teacher training, in addition to legal documents that provide content related to the topic of this research. The research is relevant for its potential to reflect on bilingual education for deaf students and on teacher training for this area of work. Another contributing factor is discussing formative paths during and after undergraduate studies to enhance teaching practice and provide more effective support for deaf students. The Libras course in teacher training programs is important not only to demystify misconceptions about deafness but also to support future teachers in adopting a more effective pedagogical practice that benefits deaf individuals in regular schools and integrates them effectively into the teaching-learning process, respecting differences and promoting education that considers the specific needs of each student. Moreover, beyond the formative aspects at the undergraduate and graduate levels, the importance of contact with and participation in the deaf community is emphasized.
Formative aspects of the bilingual educator in the education of the deaf
Keywords: Língua de Sinais; Educação de surdos; Disciplina de Libras; Formação do pedagogo bilíngue; Sign Language; Deaf education; Libras course; Bilingual teacher training; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO